Exploring learning innovation through design thinking to improve geometry problem-solving skills - Anto, Andi Timor Lusiyati; Dwijayanti, Ida; Nugroho, Aryo Andri (Fakultas Tarbiyah Universitas Ibrahimy, 2025)
This study aims to provide innovative learning solutions for schools in special regions that are striving to improve the quality of education, particularly in improving mathematical problem-solving skills. This study employs a design thinking approach comprising the stages of empathise, define, ideate, prototype, and test. This study consisted of mathematics students and teachers from schools in special areas in Sumba, East Nusa Tenggara, namely SMP Negeri 2 Wewewa Timur, SMP Negeri 3 Wewewa Timur, and SMP Negeri 2 Wewewa Tengah, as well as several other schools whose teachers are members of the Mathematics Teacher Working Group (MGMP). The respondents included 99 students from the three schools and 19 mathematics teachers. Data collection methods included questionnaires, interviews, and observations with the respondents. The findings of this study, considering the conditions and facilities of the schools, indicate that to improve geometric mathematical problem-solving skills in special regions, the following solutions are required: (1) designing E-Modules for CTL-based ethnomathematics learning, (2) developing CTL and PBL learning activities using the CRT approach based on Augmented Reality, and (3) integrating CTL with the CRT approach using GeoGebra as a medium.